Compatibility of Legal Position to Implement The New Urban Agenda in Indonesia: Adoption of Participatory Planning Decision-Making - Inna Junaenah; Ishak, Suhaili (International Journal of Environment, Architecture, and Societies, 2025)
The urbanisation of the contemporary world reveals urban challenges, for example, inequalities in spatial distribution, and Indonesia is no exception. One of the challenges is the insufficient opportunity for participation in planning decision-making. Country leaders worldwide agree to address their urban challenges by applying the New Urban Agenda (NUA) to accelerate Goal 11 of the 2030 Agenda for Sustainable Development (SDGs). This article aims to emphasize the extent of public participation in the NUA to enrich the relevant legal improvements and promote prospective enhancements to regulate public participation in planning decision-making as a right to participate in public life. A legal doctrine design, a library-based approach, and the NUA standard are applied to examine the existing laws resting on urban planning, local government, and human rights law regimes. Accordingly, the public participation setting in planning decision-making requires the NUA standard to include the key features of “equal treatment”, “design and implementation”, “evaluation”, and “effective remedies”. The study suggests that the legal compatibility in Indonesia is insufficient to accommodate those NUA standards. Therefore, it contributes to developing legal compatibility in Indonesia, which should foster citizens’ enjoyment of public participation in spatial planning decision-making towards the actualization of the NUA.